Over a million students use our free study notes to help them with their homework
This quadratic equation is in the form ax^2+bx+c=0 (a=2, b=3, c=1), where there is a coefficient in front of X2 term. First we have to multiply a and c. we then have to find two numbers z and y...
example quadratic eqn: ax2+bx+c=0 => x = (-b+-(b2-4ac)1/2)/2a <...
We can rewrite this as (5x - 2y)(5x - 2y). Now all we have to do is expand the brackets. We can do this by multiplying all the terms in the second bracket by all the terms in the first bracket and then su...
We will call sandwiches S and packets of crisps C. These are the 'unknowns'. From the information we can write down two equations. Equation 1: 3S + 2C = 9 and Equation 2: 5S + 6C = 19. We need two equatio...
If d is directly proportional to the square of t, we write this as d= kt2 , where k = the proportionality constant which we must find. Substitute in the values given in the question into our e...
←
432
433
434
435
436
→
Internet Safety
Payment Security
Cyber
Essentials